Fatty acid conjugated vaccine antigen for enhanced thermal stability and self- assembled nanonization - 김연호 (The Graduate School, Ajou University, 2024)
This study aimed to evaluate the enhanced thermal stability and physicochemical properties of fattigated vaccine antigens. High molecular weight influenza hemagglutinin (Heg) was selected as a model vaccine antigenbecause it is heat labile and requires costly storage conditions, such as a cold chamber.. The fattigated Heg was prepared by conjugating long chain oleic acid (C18) and short chain 3-decenoic acid (C10) to Heg. After conjugation, circular dichroism (CD) analysis revealed no significant changes in the three-dimensional structures. Additionally, when dispersed in a liquid state, the fattigated Heg was self-assembled due to form nanoparticles (NPs) due to its amphiphilic nature. The size of the self-assembled oleic acid- conjugated Heg (HOC) in the liquid state was approximately (136.27 ± 12.78) nm, while 3-decenoic acid conjugated Heg (HDC) was approximately (88.73 ± 3.27) nm. Heg conjugated with fatty acids exhibited higher thermal stability in various liquid and solid states than Heg alone in an accelerated thermal analysis at 60 °C for 7 days. The longer chained HOC in the liquid state exhibited better thermal stability than the shorter chained HDC. This improvement was attributed to increased hydrophobic interactions during self-assembly, suggesting that the chain length of fatty acids could impact thermal stability. Furthermore, when evaluating the thermal stability of bio-mimicking liquid states: pH 7.2 phosphate-buffered saline (PBS), 5% human serum albumin (HSA)/PBS, and 5% HSA/PBS/esterase enzyme) at 37 °C, HOC had a higher thermal stability than Heg. Based on a solid-state thermal stability analysis with or without cryoprotectants (trehalose, mannitol, tween 80), the thermal stability of HOC-containing cryoprotectants significantly increased as the externally bound fatty acids reduced the exposed surface area of the protein via nanonization. Overall, the fattigation platform could increase the thermal stability of various heat-labile vaccine antigens, thereby serving as a promising technology for vaccine development.
학위논문(석사)--약학과,2024. 2
Keywords: Hemagglutinin; accelerated thermal stability; fattigation platform; fatty acid chain length; self-assembled nanonization; vaccine antigen